2021
DOI: 10.2196/23069
|View full text |Cite
|
Sign up to set email alerts
|

A Co-Designed Active Video Game for Physical Activity Promotion in People With Chronic Obstructive Pulmonary Disease: Pilot Trial

Abstract: Background People with chronic obstructive pulmonary disease (COPD) who are less active have lower quality of life, greater risk of exacerbations, and greater mortality than those who are more active. The effectiveness of physical activity interventions may facilitate the addition of game elements to improve engagement. The use of a co-design approach with people with COPD and clinicians as co-designers may also improve the effectiveness of the intervention. Object… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The key characteristics of the enrolled studies are shown in Multimedia Appendix 2 . This review eventually consisted of 11 studies published between 2011 and 2021 with 8 RCT studies [ 18 - 22 , 30 - 32 ] and 3 pre-post studies [ 33 - 35 ]. Of the 11 studies, 3 were published in Chinese [ 21 , 22 , 32 ], and the remaining were reported in English [ 18 - 20 , 30 , 31 , 33 - 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The key characteristics of the enrolled studies are shown in Multimedia Appendix 2 . This review eventually consisted of 11 studies published between 2011 and 2021 with 8 RCT studies [ 18 - 22 , 30 - 32 ] and 3 pre-post studies [ 33 - 35 ]. Of the 11 studies, 3 were published in Chinese [ 21 , 22 , 32 ], and the remaining were reported in English [ 18 - 20 , 30 , 31 , 33 - 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This review eventually consisted of 11 studies published between 2011 and 2021 with 8 RCT studies [ 18 - 22 , 30 - 32 ] and 3 pre-post studies [ 33 - 35 ]. Of the 11 studies, 3 were published in Chinese [ 21 , 22 , 32 ], and the remaining were reported in English [ 18 - 20 , 30 , 31 , 33 - 35 ]. The countries undertaking the interventions varied greatly, including mainland China in 3 studies [ 21 , 22 , 32 ], Canada in 2 studies [ 30 , 35 ], the United States in 2 studies [ 33 , 34 ], Australia in 1 study [ 18 ], Italy in 1 study [ 31 ], Poland in 1 study [ 19 ], and Indonesia in 1 study [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The necessary level of users' engagement to achieve serious games' learning and behavioral objectives remain empirical questions (Hookham & Nesbitt, 2019;Thomas et al, 2020b). Game engagement can be operationalized by the length of time a user spends on the game (time) (Gorini et al, 2015), the frequency of repeating various game features (depth) (Sharifzadeh et al, 2020), or the completion rates of all game features (breadth) (Simmich et al, 2021). Moreover, evidence is inconsistent on the relationship between the amount of time spent by patients on serious games and intended learning outcomes (Maheu-Cadotte et al, 2021;Pham et al, 2019).…”
Section: Serious Game Engagementmentioning
confidence: 99%
“…http://www.hts.org.za Open Access through the Our Moderate Game (OMG) app makes it easy for users to still be able to play at home. This game application facilitates the delivery of message goals and can provide feedback on achievements (Simmich et al 2021;Riboli et al 2022;Thai, Bang & Li 2021). Disseminating information through interactive game applications can share ideas and experiences (Al-Dmour et al 2020).…”
Section: Introductionmentioning
confidence: 99%